MENINGKATKAN HASIL BELAJAR IPA MATERI SISTEM REPRODUKSI MANUSIA MELALUI PENERAPAN ASSESMEN PORTOFOLIO TERHADAP SISWA KELAS IX-1 - Muhammad Kasang (Universtas Negeri Makassar, 2022)
This study aims to improve the science learning outcomes of the Human Reproductive System material through the application of Portfolio Assessment to class IX-1 students. This action research was carried out in 2 cycles where the subjects in the study were 32 students of class IX-1 in the Odd Semester of the 2021/2022 Academic Year. Each cycle is carried out an assessment of the results of portfolios, tests and student participation during the learning process. Actions taken to improve learning outcomes in each cycle by motivating students to be more active in completing assignments and tests given by building cooperation and guiding each other in understanding the subject matter. The learning outcomes test in Cycle I reached 74.9 to 79.7 in Cycle II, the average student portfolio assessment score from 77.3 in Cycle I to 81.4 in Cycle II. The results showed that the application of Portfolio Assessment improved the science learning outcomes of Human Reproductive System Materials for students in class IX-1 UPTD SMP Negeri 6 Barru, Barru Regency